Life-Threatening Anemia and Thrombocytopenia in a Toddler with Influenza B: Case Report and Literature Review - Irina Profir; Cristina-Mihaela Popescu; Iuliana Moraru (Children)
Background: Seasonal influenza viruses are primarily known for causing respiratory illness, but rare hematologic complications can occur, especially in young children. While influenza A is more commonly linked to severe manifestations, influenza B can similarly precipitate life-threatening cytopenias, particularly in toddlers. Case Presentation: We report the case of a previously healthy 1-year-and-8-months-old girl who presented with a high fever, cough, and marked pallor during peak influenza season. Laboratory tests revealed significant microcytic, hypochromic anemia and severe thrombocytopenia. Rapid antigen testing was positive for influenza B. An extensive workup for other causes of bicytopenia, including leukemia, hemolysis, aplastic anemia, and other viral infections, yielded negative results. The child was managed with urgent red blood cell and platelet transfusions, oseltamivir antiviral therapy, broad-spectrum antibiotics, corticosteroids, and supportive care. Bone marrow aspiration was deferred in light of the rapid hematologic recovery. Her hemoglobin greatly improved, and her platelet count reached normal values at discharge. Conclusions: Our case underscores the need to consider influenza in the differential diagnosis of unexplained cytopenias during flu season. This case illustrates that influenza B can mimic hematologic malignancies. Rapid diagnosis and supportive treatment are essential to avoid fatal outcomes. Influenza vaccination plays a significant role in preventing severe complications, such as those we encountered.